Recent results on biomedical problems: A Fourier transform infrared (FT‒IR) study. Issue 3 (2002) - Crupi Crupi, V. V.; Galli Galli, S. S.; Majolino Majolino, D. D.; Migliardo Migliardo, P. P.; Pergolizzi Pergolizzi, S. S.; Venuti Venuti, V. V.
Abstract : In the present work, we report on a vibrational study performed on rat encephalon samples and on human tissue affected by cancer, using Fourier Transform Infrared absorbance spectroscopy. As the brain rat tissue is concerned, the FT-IR measurements, performed in the CH–OH vibrational stretching region (2400–3800 cm −1 ), permitted us to reveal the presence of a very diffuse commercial benzodiazepine: VALIUM ® . The comparison between the spectral features of normal brain and the ones of samples with administrated substance has unambiguously showed that the CH stretching region seems not to be affected by any change for the pharmacological treatment, instead the OH band is strongly modified probably due to the presence of a new spectral contribution characteristic of diazepam molecule. In the case of skin tissue the investigation was addressed to characterize the presence of two different pathologies, namely epithelioma and basalioma, and to show clear different spectral features passing from the normal tissue to the malignant one in particular in the region (1500–2000 cm −1 ) which is typical of the lipids vibrational bands.